A Practical Comparison of Waqf (Islamic Endowment) in Indonesia and Other Countries - Nila Sulistiawati; Rini Rini; Muh. Nadratuzzaman; Euis Amalia (CV. Publikasi Indonesia, 2023)
The definition of waqf in one of the results of this study is